Electron Transfer in Subunit NuoI (TYKY) of Escherichia coli NADH:Quinone Oxidoreductase (NDH-1) - Sinha, Prem Kumar (American Society for Biochemistry and Molecular Biology, 2012)
Bacterial proton-translocating NADH:quinone oxidoreductase (NDH-1) consists of a peripheral and a membrane domain. The peripheral domain catalyzes the electron transfer from NADH to quinone through a chain of seven iron-sulfur (Fe/S) clusters. Subunit NuoI in the peripheral domain contains two [4Fe-4S] clusters (N6a and N6b) and plays a role in bridging the electron transfer from cluster N5 to the terminal cluster N2. We constructed mutants for eight individual Cys-coordinating Fe/S clusters. With the exception of C63S, all mutants had damaged architecture of NDH-1, suggesting that Cys-coordinating Fe/S clusters help maintain the NDH-1 structure. Studies of three mutants (C63S-coordinating N6a, P110A located near N6a, and P71A in the vicinity of N6b) were carried out using EPR measurement. These three mutations did not affect the EPR signals from [2Fe-2S] clusters and retained electron transfer activities. Signals at g(z) = 2.09 disappeared in C63S and P110A but not in P71A. Considering our data together with the available information, g(z,x) = 2.09, 1.88 signals are assigned to cluster N6a. It is of interest that, in terms of g(z,x) values, cluster N6a is similar to cluster N4. In addition, we investigated the residues (Ile-94 and Ile-100) that are predicted to serve as electron wires between N6a and N6b and between N6b and N2, respectively. Replacement of Ile-100 and Ile-94 with Ala/Gly did not affect the electron transfer activity significantly. It is concluded that conserved Ile-100 and Ile-94 are not essential for the electron transfer.